A regulação da previdência complementar fechada sob a perspectiva da economia comportamental: e a adesão automática como proposta para a mitigação de vieses cognitivos - Martins, Luis Felipe Lopes (2015)
The present dissertation looks into the use of measures as the automatic enrolment in the pension funds regulation from the perspective of the loosening of the concept of rationality, based on the Law and Behavional Economics. The work is initiated by the historical evolution of Brazilian pension funds’ regulations. It analyzes the systemic impacts created by changes to the pension pillars, particularly to the first one (public pension). In view of these changes and the increasing relevance of the second pillar (occupational pension) to ensure the welfare, this dissertation aims to analyze the possibility of occurrence of cognitive biases in complementary pensions-related decisions. Those cognitive biases can lead individuals to choose options that do not maximize their welfare, for reasons such as inertia, procrastination and optimism, unlike the predicted by the rationality assumption of the neoclassical economic theory. The outcomes analyzed indicate the necessity of regulatory measures to mitigate these cognitive biases, which should be mainly the adoption of a choice arquitecture that can induce the welfare maximization, without limit the individual freedom of choice. Those measures, however, specially the automatic enrollment, are intended to alleviate the cognitive biases, being censurable its adoption in pension plans with predominance of other reasons to the low levels of enrollment, as distrust in the fund administration. Moreover, is needed to respect certain criteria in the automatic enrollment implementation, in order to ensure that this instrument is used only when cognitive biases that reduce the welfare are observed, as well that the option that people are being nudged to is a gainful option, at least most of the times. At end, it is verified the legality of these measures using the standard of proportionality, which allows to identify the limits to the regulatory intensity.